2013
DOI: 10.3109/13816810.2013.843712
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism Analysis ofVSX1andSOD1Genes in Greek Patients with Keratoconus

Abstract: We cannot confirm the previously reported association of the polymorphism in the VSX1 gene with KC. Our results suggest a possible causative role of SOD1 in the pathogenesis of KC. Further studies are required to identify other important genetic factors involved in the pathogenesis and progression of KC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 27 publications
2
19
0
3
Order By: Relevance
“…R166W and H244R VSX1 variants might play critical role in the pathogenesis of keratokonic corneas, as suggested by SaeeRad et al [53]. The same study group identified three novel SNPs (g. 4886G>A, g.4990C>G, and g.9061T>A) in SOD1, but these SNPs did not seem to influence the activity of SOD1 protein [53]. Czugala et al detected four substitutions in three different genes: c.2262A>C (p.Gln754His) and c.720+43A>G in DOCK9; c.2377-132A>C in IPO5 and c.1053+29G>C in Serine/threonine-protein kinase (STK24) [54].…”
Section: Other Genes Implicated In Keratoconus Pathogenesismentioning
confidence: 57%
See 1 more Smart Citation
“…R166W and H244R VSX1 variants might play critical role in the pathogenesis of keratokonic corneas, as suggested by SaeeRad et al [53]. The same study group identified three novel SNPs (g. 4886G>A, g.4990C>G, and g.9061T>A) in SOD1, but these SNPs did not seem to influence the activity of SOD1 protein [53]. Czugala et al detected four substitutions in three different genes: c.2262A>C (p.Gln754His) and c.720+43A>G in DOCK9; c.2377-132A>C in IPO5 and c.1053+29G>C in Serine/threonine-protein kinase (STK24) [54].…”
Section: Other Genes Implicated In Keratoconus Pathogenesismentioning
confidence: 57%
“…However, in the same study the SOD1 intronic 7-base deletion (c.169 + 50delTAAACAG) was over-represented among keratoconic patients compared to healthy controls [52]. R166W and H244R VSX1 variants might play critical role in the pathogenesis of keratokonic corneas, as suggested by SaeeRad et al [53]. The same study group identified three novel SNPs (g. 4886G>A, g.4990C>G, and g.9061T>A) in SOD1, but these SNPs did not seem to influence the activity of SOD1 protein [53].…”
Section: Other Genes Implicated In Keratoconus Pathogenesismentioning
confidence: 70%
“…To test for the presence of the intronic 7-base deletion IVS2 + 50del7bp (c.169+50delTAAACAG) in SOD1, samples were tested by PCR in 140 KC positive patients and 120 controls, using previously described amplification conditions. [29] Detection of this deletion in patients involved direct visualization of a 211 bp amplicon in a 20 x 20 cm PAGE (5%) electrophoresis, followed by confirmatory DNA sequencing of positive samples.…”
Section: Dna Sequencingmentioning
confidence: 99%
“…[26] Several studies have described a heterozygous genomic 7-base deletion in the intron 2 of the SOD1 gene (IVS2 + 50del7bp) in the US population which significantly affected the conformation and function leading to an increase in oxidative stress in the cornea. [27][28][29] Two sporadic carriers of this deletion were also detected in the Italian population, [30] and nine in the Greek population. [29] The involvement of SOD1 in other ocular diseases such as primary open-angle glaucoma has also been described.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation